Surgical Neutering of a Tom Cat during Clinical Camp - Brahmbhatt, Ankita; Patel, Sanjay; Suthar, Vishal (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Castration or neutering in male pet animals is generally not practiced unless there is any testicular pathology or as a  contraceptive means (Howe et al., 2000; Howe, 2015; Monin  et  al., 2019). Kamdhenu University, Gandhinagar operates  an ambulatory clinic at village Sanoda, Tehsil Dehgam,  Dist Gandhinagar, Gujarat and also participates in animal  health and infertility camps treating large (Kapadiya et al.,  2019; Brahmbhatt et  al., 2020) and small animals (Mahesh  et al., 2016, Momin et al., 2019). The pet canines presented  in clinical camps are very less and felines are rarely brought  for any medication or interventions in such camps. In this  document such a rare case of 2 years old tom cat presented  and successfully operated for neutering at the ambulatory  clinic in a village without referring to secondary or tertiary  set up is reported and discussed.
Keywords: Clinical camp; Neutering; Normal recovery; Tom cat